2016
DOI: 10.1007/s00011-016-0993-3
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic regulations of neutrophil receptors response to sepsis

Abstract: Neutrophil receptors play key roles in chemotactic neutrophil migration and may prove to be suitable targets in future pharmacological therapies for sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 108 publications
0
6
0
1
Order By: Relevance
“…However, treatment of sepsis remains a prominent challenge to clinical practice. Numerous studies focusing on the pathophysiology of sepsis have revealed an imbalance in the inflammatory network, leading to tissue damage, organ failure and ultimately death (Zhang & Sun, ). During the disease progression, many metabolisms (energy metabolism, glycogen syntheses, lipid metabolism, and purine metabolism) are modulated in response to stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment of sepsis remains a prominent challenge to clinical practice. Numerous studies focusing on the pathophysiology of sepsis have revealed an imbalance in the inflammatory network, leading to tissue damage, organ failure and ultimately death (Zhang & Sun, ). During the disease progression, many metabolisms (energy metabolism, glycogen syntheses, lipid metabolism, and purine metabolism) are modulated in response to stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil migration at sites of inflammation is mediated by various chemoattractant receptors, mainly the formyl‐peptide receptors (FPRs), CXC chemokine receptors (CXCRs) and complement factor 5a (C5a) 24 . The formyl‐peptide receptor (FPR) gene cluster in humans has three members: FPR1, FPRL1 and FPR2 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning the modulation of neutrophil activity by cannabinoids during infections are mostly addressed to experimental bacterial infection as sepsis model. Neutrophil activity during experimental sepsis is well characterized in studies in vivo (to review [97][98][99]). By using LPS sepsis model, Smith and coworkers showed that treatment with cannabinoid receptor agonists reduced the migration of neutrophils in the peritoneal cavity by inhibiting neutrophil chemoattractant production [59].…”
Section: Neutrophils Cannabinoid System and Infectionmentioning
confidence: 99%